2020
DOI: 10.3892/etm.2020.8718
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin alleviates TNBS‑induced colitis by inhibiting PI3K/AKT pathway activation

Abstract: Inflammatory bowel diseases (IBDs) are chronic immunological disorders of the intestinal tract characterized by persistent inflammation. Baicalin, a type of flavonoid, has exhibited a wide range of pharmacological activities, including immunomodulation and anti-inflammation. However, little is known about the therapeutic role of baicalin in IBD. The aim of the present study was to ascertain whether baicalin could be a therapeutic drug of IBD and investigate its specific mechanisms. In the present study, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 54 publications
4
29
0
1
Order By: Relevance
“…The produced cytokines can be released and cause further cycles of cytokine amplification that is harmful in acute inflammation condition, such as in COVID-19. According to previous reports, baicalin regulates the PI3K/AKT signal [24] and NF-κB [23,43], and these activities may be responsible for baicalin-induced anti-inflammatory effect [16,23,43]. Our analysis and the supportive data from the literature suggested that baicalin may protect the cell from pro-inflammatory factors, such as cytokine and chemokine, through disrupting several inflammation-associated signaling pathways inside the cell.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The produced cytokines can be released and cause further cycles of cytokine amplification that is harmful in acute inflammation condition, such as in COVID-19. According to previous reports, baicalin regulates the PI3K/AKT signal [24] and NF-κB [23,43], and these activities may be responsible for baicalin-induced anti-inflammatory effect [16,23,43]. Our analysis and the supportive data from the literature suggested that baicalin may protect the cell from pro-inflammatory factors, such as cytokine and chemokine, through disrupting several inflammation-associated signaling pathways inside the cell.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, SB and several herbal formulas comprising SB were suggested as potential therapeutics to treat COVID-19 with supportive data provided from in silico approaches or system pharmacological studies [7,[19][20][21][22]. Baicalin is known to be responsible for the major biological effects of SB and exhibits anti-inflammatory and antiviral effects with low cytotoxicity [23][24][25]. Baicalin is the main composition of Flavocoxid, an approved medical food, which is classified as generally recognized as safe by regulatory requirement.…”
mentioning
confidence: 99%
“…BA is the main active ingredient of Scutellaria, and its content is generally 9%-20%. There is abundant evidence suggesting that BA exerts clear anti-inflammatory effects on a variety of inflammation models and has protective and therapeutic effects on ALI [ 24 , 25 ]. However, BA has poor aqueous solubility, which sharply decreases its bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin is an active ingredient extracted from the dried roots of Scutellaria baicalensis Georgi ( Wang et al, 2022 ). Baicalin significantly increased the activity of CAT, SOD, and GSH in colonic tissue of UC by blocking NF-κB and PI3K/Akt signaling pathways, reducing the release of IL-6, IL-1β, and TNF-α, increasing the level of IL-10, inhibiting TNBS-induced increase in ROS and MDA levels, control inflammatory responses and reduce oxidative stress damage ( Shen et al, 2019 ; Zhu et al, 2020a ). Baicalin effectively inhibits the expression of macrophage migration inhibitory factor (MIF), regulates macrophage function, promotes the proliferation of CD4 + CD29 + cells, and regulates Th17/Treg balance.…”
Section: Natural Products and Ibdmentioning
confidence: 99%